Administrative and Criminal Penalties in the Enforcement of Occupational Health and Safety Legislation - Brown, R. M. (1992)
The sanction for occupational health and safety offences in Ontario is a regulatory prosecution in provincial criminal court. In contrast, regulatory officials assess administrative penalties in British Columbia and the United States. A larger proportion of offenders are punished under these administrative processes than in the Ontario criminal justice system, and the average administrative penalty generally is higher than the average criminal fine. In addition, a system of administrative penalties is better able to identify employers who warrant punishment because regulators apply the civil standard of proof, attach great weight to a firm's compliance history, and do not reserve penalties for offences that actually result in a worker being harmed